Senators beholden to the people Lincoln and the doctrine of instruction - Miller, Richard Lawrence 1949- (McFarland & Company, Inc., Publishers, 2024)
"The republic's founders debated whether to have a government based on direct democracy (in which the general population decided public policy questions, as in a New England town meeting) or representative democracy (in which those decisions were made by senators and congressmen on behalf of the general population). A related issue was whether the general population should have the "right of instruction" which gave citizens authority to expel from office government officials who disobeyed the desires of the population. The right of instruction is now largely forgotten but in former times was considered so important that it was routinely included in state constitutions. This book examines the competition between direct democracy and representative democracy in the United States, focusing particularly on the doctrine of instruction, through the lens of the pre-presidential career of Abraham Lincoln."--
Keywords: Geschichte; Repräsentative Demokratie; Direkte Demokratie; Politisches Denken; USA; Direct democracy / United States / History; Representative government and representation / United States / History; Representative government and representation / United States / States / History; Constituent power / United States / History; Constituent power / United States / States / History; Legislative bodies / United States / States / History; United States / Congress / Senate / History; United States / Politics and government / 19th century; U.S. states / Politics and government / 18th century; U.S. states / Politics and government / 19th century; Démocratie directe / États-Unis / Histoire; Gouvernement représentatif / États-Unis / Histoire; Gouvernement représentatif / États-Unis / États / Histoire; Pouvoir constituant / États-Unis / Histoire; Pouvoir constituant / États-Unis / États / Histoire; États-Unis / Congress / Senate / Histoire; États-Unis / Politique et gouvernement / 19e siècle; HISTORY / United States / Civil War Period (1850-1877); POLITICAL SCIENCE / American Government / General